Nigel Wiseman: Modern Texts, Classics, Terminology, and Language-learning Material - Nigel Wiseman; Zhiheng GUO (Wolters Kluwer Health/LWW, 2024)
Abstract. In this article, I trace my career from an early interest in language that eventually led me to engage in Chinese medical translation. Born in the United Kingdom in 1954, I gained a Bachelor of Arts degree in German and Spanish from the University of Heriot-Watt, Edinburgh. Subsequent study of Chinese took me to Taiwan, China, where I gained an interest in Chinese medicine and developed a coherent linguistic approach to Chinese medical term translation, which I and various colleagues have systematically applied in the translation and compilation of numerous works spanning modern texts, classics, dictionaries, and language-learning materials. Our translation approach, though conforming to principles universally recognized by translation theorists, has proven to be highly controversial, with opponents in both Western and Chinese circles.